Shoulder tenderness was associated with the inflammatory changes on magnetic resonance imaging in patients with rheumatoid arthritis - Shinagawa, Satoshi (Sci Rep, 2019)
The aim of this study was to assess the association between the shoulder tenderness and the inflammatory changes on magnetic resonance imaging (MRI) in the rheumatoid shoulder. Forty-one shoulders of 41 patients with rheumatoid arthritis (RA) were examined. We evaluated synovitis, erosion and bone marrow edema, by counting the numbers of each positive site, and rotator cuff tears on shoulder MRI. The association between the shoulder tenderness and the MRI findings were statistically analyzed. Twenty-three of 41 patients had tenderness in the shoulder joints. There were 20 shoulders (48.8%) with rotator cuff tear, and no significant difference was observed in the prevalence of rotator cuff tear between the tenderness group and non-tenderness group (p = 0.080). There were no significant differences in the demographic data between these two groups. In MRI findings, we found significant difference for the synovitis (p = 0.001) and bone marrow edema (p = 0.021). Synovitis was strongly associated with the shoulder tenderness (OR: 3.996, 95% CI: 1.651–9.671). Synovitis was the factor most associated with shoulder tenderness.